2019
DOI: 10.1007/s00011-019-01273-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of palmitic acid on inflammatory response in macrophages: an overview of molecular mechanisms

Abstract: Palmitic acid is a saturated fatty acid whose blood concentration is elevated in obese patients. This causes inflammatory responses, where toll-like receptors (TLR), TLR2 and TLR4, play an important role. Nevertheless, palmitic acid is not only a TLR agonist. In the cell, this fatty acid is converted into phospholipids, diacylglycerol and ceramides. They trigger the activation of various signaling pathways that are common for LPS-mediated TLR4 activation. In particular, metabolic products of palmitic acid affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
250
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(270 citation statements)
references
References 223 publications
(282 reference statements)
11
250
1
8
Order By: Relevance
“…A higher palmitate content would likely induce a strong inflammatory response to the materials which is adverse for the arterial remodeling. [ 48,49 ] According to the synergistic effects of the reduced elastic modulus, enhanced elasticity and slower degradation, we deduce that PPGS‐9 and PPGS‐16 could meet our requirements for small arteries. We have therefore used PPGS‐9 and PPGS‐16 together with PGS to construct vascular grafts for an in vivo study in a rat carotid model.…”
Section: Resultsmentioning
confidence: 90%
“…A higher palmitate content would likely induce a strong inflammatory response to the materials which is adverse for the arterial remodeling. [ 48,49 ] According to the synergistic effects of the reduced elastic modulus, enhanced elasticity and slower degradation, we deduce that PPGS‐9 and PPGS‐16 could meet our requirements for small arteries. We have therefore used PPGS‐9 and PPGS‐16 together with PGS to construct vascular grafts for an in vivo study in a rat carotid model.…”
Section: Resultsmentioning
confidence: 90%
“…PA acts as a lipid mediator in inflammation and its derived-metabolic products accumulate in the endoplasmic reticulum (ER) and increase reactive oxygen species (ROS) generation, leading to cell death [52]. Additionally, the inflammatory response caused by ER stress and ROS generation from high concentrations of PA drives NF-κB and NLRP3 activation and, consequently, proinflammatory cytokine release by monocytes/macrophages [53][54][55][56]. S-Acetyldihydrolipoamide, N-palmitoyl serine and PE(P-16:0/00) (2-Hexadecanoyl-1-(1Z-hexadecenyl)-sn-glycero-3-phosphoethanolamine) are associated with cell metabolism [57], membrane receptor [58], and cell membrane compounds [59], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…When the increased intracellular PA level exceeds its βoxidation in mitochondria, it is converted to harmful complex lipids such as diacylglycerin (DAG) and ceramide (5,27). These harmful FA-derived intermediates and excessive PA provoke increased reactive oxygen species (ROS) production, damage the function of mitochondria-related ER membrane (MAM), and induce mitochondrial fragmentation, resulting in mitochondrial dysfunction and loss of ATP production (28)(29)(30)(31). Recently, Rambold et al reported that fragmented mitochondria failed to efficiently take up FA, causing a reduction in β-oxidation rates and further exacerbating the accumulation of FA in Mitofusin1 KO cells (15).…”
Section: Discussionmentioning
confidence: 99%